2021
DOI: 10.1108/ijrdm-08-2020-0302
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the predictors of the young buyers' satisfaction in the e-retailing apparel sector

Abstract: PurposeAs satisfaction is one of the most important conditions for loyalty, this study aims to investigate the main factors affecting online satisfaction for buying clothes from the internet. In this research, the authors followed two main objectives: (1) to identify factors influencing online satisfaction and (2) to determine the importance of the main determinants that explain online satisfaction in the retailing clothing sector.Design/methodology/approachThe research combines qualitative and quantitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 94 publications
(160 reference statements)
0
5
0
Order By: Relevance
“…The findings support that e-service quality is a significant predictor of customer satisfaction (Hypothesis 1), which provide resounding evidence to other studies (Ighomereho et al ., 2022; Bobalca et al ., 2021; Suhaily and Soelasih, 2017). It is quite logical that when e-retailers respond to customers’ complaints and concerns and provide individualized and personal services to meet their needs, they are more likely to be satisfied with the services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings support that e-service quality is a significant predictor of customer satisfaction (Hypothesis 1), which provide resounding evidence to other studies (Ighomereho et al ., 2022; Bobalca et al ., 2021; Suhaily and Soelasih, 2017). It is quite logical that when e-retailers respond to customers’ complaints and concerns and provide individualized and personal services to meet their needs, they are more likely to be satisfied with the services.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies found that e-SERVQUAL dimensions positively correlate with customer satisfaction and repurchase intention (Patwardhan and Pandey, 2021;Kulkarni et al, 2019;Rita et al, 2019). In online buying apparel, the researchers found that website reputation and service quality in e-retailing were significant predictors of satisfaction (Bobalca et al, 2021). In one of the recent studies on 318 e-channel users conducted in Nigeria, Ighomereho et al (2022) found that e-SERVQUAL dimensionswebsite appearance, ease of use, reliability, security, personalization, fulfillment and responsivenessare positively associated with customer satisfaction.…”
Section: Tqm 358mentioning
confidence: 97%
“…The results of the analysis are presented in Table 3. Based on the statistical analysis results in Table 3, the analysis of the gender variable shows that females account for 82.2%, which is convincing given that females are the primary group for online clothing shopping (Bobalca et al, 2021). The analysis of the age variable indicates that the 18-30 age group constitutes 92.6% of the samples, suggesting a valuable segment with strong purchasing power and online shopping experience.…”
Section: Descriptive Statistical Analysismentioning
confidence: 72%
“…However, studies have shown that website design, a color used for design, information availability, and convenience are not important in modifying the level of online customer experience (Bobalca et al, 2021;Krasonikolakis et al, 2018;and Kumar & Anjaly,2017). Therefore, the researchers have further investigated how website design determines online customer experience towards online shopping platforms among university students.…”
Section: Website Designmentioning
confidence: 99%
“…It is recommended that the company should provide personalized service by using human and technological resources to manage activity with customers, as well as well-prepared customer service representatives to support these activities because customers prefer to be treated as per their expectations, unique and special (Bobalca et al, 2021). Moreover, customers tend to repurchase intention from online shopping platforms when they can easily change or return unsuitable items and quickly get personalization from the company (Raman, 2019).…”
Section: Customer Servicementioning
confidence: 99%